2018
DOI: 10.1111/ctr.13306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP3A5*1 expression on tacrolimus required dose after liver transplantation: A systematic review and meta‐analysis

Abstract: We systematically collected eligible data to measure the effect of CYP3A5*1 expression on personalized tacrolimus therapy. Six databases were searched for studies on adult liver transplant recipients and donors of liver graft which reported tacrolimus dose requirement, trough blood concentration, and/or concentration/dose (C/D) ratio in expressers and nonexpressers of CYP3A5*1. Eligible data were pooled by meta-analysis. Sixteen observational studies (1309 recipients, 1044 donors of liver graft) were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 46 publications
0
19
0
1
Order By: Relevance
“…[6][7][8]14 CYP3A5 expressors carry the *1 variant which encodes the functional enzyme responsible for the metabolism of tacrolimus; therefore, they may require a higher dose of tacrolimus than the non-expressors to achieve the target trough level of the drug. [3][4][5] Our present study demonstrated that CYP3A5 polymorphism influenced both tacrolimus dose and trough level of the drug; the median dose of tacrolimus both before and after switching to the once-daily extended-release formulation was significantly higher in the expressor group than in the non-expressors. This observation is also consistent with the results of previous studies in which CYP3A5 expressors, both adult and pediatric patients, required higher doses of tacrolimus due to higher oral clearance of the drug.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…[6][7][8]14 CYP3A5 expressors carry the *1 variant which encodes the functional enzyme responsible for the metabolism of tacrolimus; therefore, they may require a higher dose of tacrolimus than the non-expressors to achieve the target trough level of the drug. [3][4][5] Our present study demonstrated that CYP3A5 polymorphism influenced both tacrolimus dose and trough level of the drug; the median dose of tacrolimus both before and after switching to the once-daily extended-release formulation was significantly higher in the expressor group than in the non-expressors. This observation is also consistent with the results of previous studies in which CYP3A5 expressors, both adult and pediatric patients, required higher doses of tacrolimus due to higher oral clearance of the drug.…”
Section: Discussionmentioning
confidence: 52%
“…CYP3A5 genotype is known to play a role in determining the effect of interacting drugs, such as fluconazole, on tacrolimus pharmacokinetics. 5 However, it needs to be stressed that our study did not analyze the issue of drug interaction, and all patients who received agents that might potentially interact with tacrolimus were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphisms that alter activity of both CYP3A5 and P‐gp in different tissues, notably the donor liver, recipient gastrointestinal tract and recipient lymphocytes could contribute to rejection and toxicity. Indeed, a recent meta‐analysis has shown that both recipient's and donor's CYP3A5 expression similarly influence tacrolimus concentrations following liver transplant . In contrast, observations relating ABCB1 genetic variability with tacrolimus concentrations remain discordant …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent meta-analysis has shown that both recipient's and donor's CYP3A5 expression similarly influence tacrolimus concentrations following liver transplant. 6 In contrast, observations relating ABCB1 genetic variability with tacrolimus concentrations remain discordant. 2 In addition to metabolism and transport of tacrolimus, the impact of innate immune responses and cytokine expression also play an important role in transplantation through modification of CYP3A and P-gp expression and/or activity.…”
Section: Introductionmentioning
confidence: 99%